Cell and Molecular Biology - Eduardo D P De Robertis (Lippincott Williams & Wilkins, 2014)
Explains the recent and evidence based guidelines for prevention of hospital associated infections published by the WHO and Centers for Disease Control and Prevention. Provides a thorough discussion of cleaning and disinfection protocols as well as isolation precautions. Highlights the growing threat from device associated infections and presents measures for their prevention. Discuss the problems related to the multi drug resistance, emerging infections and agents of the bio- terrorism. Highlights infections in trauma as well as immune compromised patients, especially vulnerable to hospital associated infections. Presents the advances in surveillance systems in relation to preventive programmers for hospital associated infections. Discuss relevant issues relating to Biomedical waste management and disposal.